2022
DOI: 10.3389/ffutr.2022.893583
|View full text |Cite
|
Sign up to set email alerts
|

Electric vehicle charging infrastructures in the Greater Bay Area of China: Progress, challenges and efforts

Abstract: The electric vehicle (EV) has proven to be a workable solution to minimizing environmental pollution. The EV has generally received substantial attention from both individual customers and corporate users. The EV has transformed remarkably and in recent years emerged as the most quickly developing section of the automobile industry. China has proven to be an outstanding country in enhancing the manufacture and marketing of EVs. Nevertheless, green environment, charging infrastructure and technology are the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…As such, decision makers and scientists globally are concentrating on sustainable ground transportation to decrease CO 2 emissions and balance the climate. Lau et al [16,17] suggested an energy shift to reduce CO 2 emissions and employ electric vehicles in road transportation. Epicoco and Falagario [13] addressed that the railway is identified as one of the most sustainable and environmentally friendly transport modes, and increasing the efficiency of regional and local railways is a prime sustainable ground transportation goal.…”
Section: Literature Review On Sustainable Ground Transportationmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, decision makers and scientists globally are concentrating on sustainable ground transportation to decrease CO 2 emissions and balance the climate. Lau et al [16,17] suggested an energy shift to reduce CO 2 emissions and employ electric vehicles in road transportation. Epicoco and Falagario [13] addressed that the railway is identified as one of the most sustainable and environmentally friendly transport modes, and increasing the efficiency of regional and local railways is a prime sustainable ground transportation goal.…”
Section: Literature Review On Sustainable Ground Transportationmentioning
confidence: 99%
“…This trend bolsters sustainability efforts and propels electric vehicle technology and infrastructure enhancement [8]. Secondly, the high demand for delivery efficiency in e-commerce has catalysed the evolution of route optimisation and logistics strategies [17,48]. These advancements focus on reducing travel distances and fuel consumption, reducing emissions, and easing urban traffic congestion.…”
Section: Influences Of E-commerce On Sustainable Ground Transportationmentioning
confidence: 99%
“…In China, a slight decrease in private charging stations is attributed to profitability issues during peak-hour periods [10]. Battery capacity requirements vary based on operating routes, with higher capacities necessitating cost comparisons with charging infrastructure and bus schemes [11].…”
Section: Electric Battery Buses In Public Transportationmentioning
confidence: 99%
“…The environmental driver is usually the main one for sustaining BEV for LPT in the literature: in [23], the authors underline how BEVs have proven to be a workable solution for minimizing environmental pollution and how the BEV has generally received substantial attention from both individual customers and corporate users; nevertheless, the green environment, charging infrastructure and technology are the three main challenges leading to the slowing down of the progress of the penetration of BEVs into the Greater Bay Area (GBA) of China.…”
Section: Literature Reviewmentioning
confidence: 99%